2016
DOI: 10.1016/j.bbr.2015.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic α7 and α4β2 agonists enhance the formation and retrieval of recognition memory: Potential mechanisms for cognitive performance enhancement in neurological and psychiatric disorders

Abstract: In the current study we investigated the efficacy of donepezil, risperidone and selective nicotinic α7 and α4β2 receptor agonists to reverse a delay-induced deficit in recognition memory. Adult female hooded-Lister rats received drug treatments and were tested in the novel object recognition (NOR) task following a 6 hour inter-trial interval (ITI). In all treatment groups there was no preference for the left or right identical objects in the acquisition trial. In the retention trial vehicle, risperidone (0.16m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 72 publications
2
19
0
Order By: Relevance
“…The brain regions thought to be involved in object recognition memory depend on the length of the inter-trial interval (ITI). We have recently shown that normal unimpaired animals lose the ability to discriminate objects following an ITI of 6 hours (McLean et al, 2016). Rats with hippocampal lesions exhibit impairments in object recognition following long ITIs (>15 min), but not short intervals of <15 min (Clark et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The brain regions thought to be involved in object recognition memory depend on the length of the inter-trial interval (ITI). We have recently shown that normal unimpaired animals lose the ability to discriminate objects following an ITI of 6 hours (McLean et al, 2016). Rats with hippocampal lesions exhibit impairments in object recognition following long ITIs (>15 min), but not short intervals of <15 min (Clark et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…5). Moreover, dFBr (1.0 or 3.0 mg/kg) reversed the impairing effects elicited by scopolamine (a two-way ANOVA interaction for exploration time: F [3,29] = 8.99, p < 0.001; Supplementary Table 1 S2, and a one-way ANOVA interaction for DI: F [3,29] = 10.76, p < 0.001; Fig. 6).…”
Section: Desformylflustrabromine Reverses Ketamineand Scopolamine-indmentioning
confidence: 87%
“…For example, the ability to discriminate between a novel object and a familiar object after a 24-h delay was improved by TC-1734 (AZD3480, ispronicline) in mice [32] and by TC-6683 (AZD1446) in rats [33]. The administration of 0.1 mg/kg TC-2403 reversed 6 h ITI-induced forgetting in rats [29]. Although the efficacy of TC-2403 was also supported in the current study (Supplement 1), the active dose was higher (i.e., 0.3 mg/kg) than that used by McLean et al [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations